Peristilahan Kekerabatan Sunda Kuna dan Rekonstruksi Etnoarkeologi atas Hukum Keluarga Masyarakat Sunda Kuna - Dede - Mulyanto (PURBAWIDYA: Jurnal Penelitian dan Pengembangan Arkeologi, 2019)
The research underlying this paper aims to reconstruct Old Sundanese kinship terminology and its consequences on the family law of the Old Sundanese community. Genealogical method was used to found kin terms and to reconstruct its structural features. From four manuscripts that have been studied, there were 25 term of refferences for 17 kin categories. Basically, old Sundanese kinship terminology have strong characteristics toward lineal-Eskimo type of terminology in which term of refferences for kins in nuclear family circle more descriptive and more classificatorist for other kins outside it. Balance distributions on kolateral kins also important in this type. Compared with contemporary Sundanese, there are no structural changes in Sundanese kinship terminology. Theoritically, the consequence of bilaterality in kinship terminology is parental nature of its family law. Probably, old Sundanese society also parental in their family law. .